Gene expression of S100a8/a9 predicts Staphylococcus aureus-induced septic arthritis in mice - Deshmukh, Meghshree; Subhash, Santhilal; Hu, Zhicheng; Mohammad, Majd; Jarneborn, Anders; Pullerits, Rille; Jin, Tao; Kopparapu, Pradeep Kumar (Frontiers in Microbiology, 2023)
Septic arthritis is the most aggressive joint disease associated with high morbidity and mortality. The interplay of the host immune system with the invading pathogens impacts the pathophysiology of septic arthritis. Early antibiotic treatment is crucial for a better prognosis to save the patients from severe bone damage and later joint dysfunction. To date, there are no specific predictive biomarkers for septic arthritis. Transcriptome sequencing analysis identified S100a8/a9 genes to be highly expressed in septic arthritis compared to non-septic arthritis at the early course of infection in an S. aureus septic arthritis mouse model. Importantly, downregulation of S100a8/a9 mRNA expression at the early course of infection was noticed in mice infected with the S. aureus Sortase A/B mutant strain totally lacking arthritogenic capacity compared with the mice infected with parental S. aureus arthritogenic strain. The mice infected intra-articularly with the S. aureus arthritogenic strain significantly increased S100A8/A9 protein expression levels in joints over time. Intriguingly, the synthetic bacterial lipopeptide Pam2CSK4 was more potent than Pam3CSK4 in inducing S100A8/A9 release upon intra-articular injection of these lipopeptides into the mouse knee joints. Such an effect was dependent on the presence of monocytes/macrophages. In conclusion, S100A8/A9 may serve as a potential biomarker to predict septic arthritis, enabling the development of more effective treatment strategies.